Freely Expanding Knots of X-Ray-emitting Ejecta in Kepler's Supernova Remnant - Sato, Toshiki; Hughes, John P. (The Astrophysical journal, 2017)
We report measurements of proper motion, radial velocity, and elemental composition for 14 compact X-ray-bright knots in Kepler's supernova remnant (SNR) using archival Chandra data. The knots with the highest speed show both large proper motions ( ∼ 0 11-0 14 yr−1) and high radial velocities (v ∼ 8700-10,020 km s−1). For these knots the estimated space velocities (9100 km s−1 v3D 10,400 km s−1) are similar to the typical Si velocity seen in supernovae (SNe) Ia near maximum light. High-speed ejecta knots appear only in specific locations and are morphologically and kinematically distinct from the rest of the ejecta. The proper motions of five knots extrapolate back over the age of Kepler's SNR to a consistent central position. This new kinematic center agrees well with previous determinations, but is less subject to systematic errors and denotes a location about which several prominent structures in the remnant display a high degree of symmetry. These five knots are expanding at close to the free expansion rate (expansion indices of 0.75 m 1.0), which we argue indicates either that they were formed in the explosion with a high density contrast (more than 100 times the ambient density) or that they have propagated through regions of relatively low density (nH < 0.1 cm−3) in the ambient medium. X-ray spectral analysis shows that the undecelerated knots have high Si and S abundances, a lower Fe abundance, and very low O abundance, pointing to an origin in the partial Si-burning zone, which occurs in the outer layer of the exploding white dwarf for models of SNe Ia. Other knots show lower speeds and expansion indices consistent with decelerated ejecta knots or features in the ambient medium overrun by the forward shock. Our new accurate location for the explosion site has well-defined positional uncertainties, allowing for a great reduction in the area to be searched for faint surviving donor stars under non-traditional single-degenerate SNe Ia scenarios; because of the lack of bright stars in the search area the traditional scenario remains ruled out.